2007
DOI: 10.1002/bem.20343
|View full text |Cite
|
Sign up to set email alerts
|

Permeability changes induced by 130 GHz pulsed radiation on cationic liposomes loaded with carbonic anhydrase

Abstract: The effects of pulsed 130 GHz radiations on lipid membrane permeability were investigated by using cationic liposomes containing dipalmitoyl phosphatidylcholine (DPPC), cholesterol, and stearylamine. Carbonic anhydrase (CA) was loaded inside the liposomes and the substrate p-nitrophenyl acetate (p-NPA) added in the bulk aqueous phase. Upon permeation across the lipid bilayer, the trapped CA catalyzes the conversion of the p-NPA molecules into products. Because the self-diffusion rate of p-NPA across intact lip… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
36
0

Year Published

2008
2008
2022
2022

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 50 publications
(38 citation statements)
references
References 33 publications
0
36
0
Order By: Relevance
“…In this context, we studied the effects of THz radiation on the permeability of a membrane model system (liposome), which, in contrast to living cells, is well defined and only has a limited number of parameters, allowing an accurate evaluation of membrane effects induced by electromagnetic radiation [41]. The effects induced by 0.13 THz radiation pulse-modulated at low frequencies of 5, 7 or 10 Hz, and at timeaveraged incident intensity (I AV ) up to 17 mW/cm 2 was studied in real-time during the irradiation.…”
Section: Thz Radiation Effects On Biological Systemsmentioning
confidence: 99%
“…In this context, we studied the effects of THz radiation on the permeability of a membrane model system (liposome), which, in contrast to living cells, is well defined and only has a limited number of parameters, allowing an accurate evaluation of membrane effects induced by electromagnetic radiation [41]. The effects induced by 0.13 THz radiation pulse-modulated at low frequencies of 5, 7 or 10 Hz, and at timeaveraged incident intensity (I AV ) up to 17 mW/cm 2 was studied in real-time during the irradiation.…”
Section: Thz Radiation Effects On Biological Systemsmentioning
confidence: 99%
“…Changes on the permeability of lipid bilayer membranes were reported by RamundoOrlando et al [47]. The effects induced by 130 GHz radiations, pulse-modulated at low frequencies of 5, 7 or 10 Hz, and at time-averaged incident intensity (I AV ) up to 17 mW/cm 2 were studied in real-time during the irradiation of cationic liposomes loaded with carbonic anhydrase.…”
Section: Cell Membrane: the Major Target Of Mmw Interactionmentioning
confidence: 92%
“…Set of experiments with the use of a coloring material which does not penetrate through intact membranes (Trypan Blue), and reveals living cell, and electrophysiological analyze showed that THz irradiation creates conditions for penetrating of those substances into living cells, which do not usually penetrate [25]. Besides, it had been established that penetrance of phospholipid liposomes increases significantly after 130 GHz irradiation with density 10-17 mW/cm² [26].…”
Section: Subcellular Level Of Effects Realization Of Thz Wavesmentioning
confidence: 99%